Performance of an Application Layer Protocol for Wireless Industrial Communications - Carreras, I.; Miorandi, D.; Vitturi, S. (2006 IEEE Conference on Emerging Technologies and Factory Automation, 2006)
Current wireless technologies offer a viable solution for implementing communication systems capable of satisfying the severe timing requirements often required for operations at the lowest levels of factory automation systems. Most of the contributions appeared in the literature on this subject aimed at investigating the suitability to industrial applications of some wireless communication protocols. In this paper, we address the problem from a different perspective. Namely, we are interested in characterizing the application layer performance of a field-bus protocol running over an IEEE 802.11g-based wireless LAN. We provide a preliminary Java-based implementation of such application protocol, and test it on laptops running a Linux operating system and off-the-shelf 802.11 cards. The performance of the application layer protocol are extensively tested on an experimental system characterized by environmental conditions similar to those of industrial installations.